The Storytelling Technique Is A Method For Developing Creative Thinking And Skills - F.M.Turakulova (Zien Journals, 2026)
This study examines the importance of using storytelling techniques in the educational process in developing students' creative thinking and personal skills. During the research, the scientific literature on the topic was analyzed and the effectiveness of storytelling techniques was determined through experimental studies. The results obtained confirm that story-based activities have a positive impact on the development of students' independent thinking, speech activity, imagination, and creative approach.
Keywords: storytelling; creative thinking; teaching methods; personal skills